Analyzing Growth Mindset Based on Opportunity to Learn in Project-Based Manipulative and Virtual Learning Media Courses - Nasrullah, Nasrullah; Arsyad, Nurdin; Alimuddin, Alimuddin (Lafadz Jaya Publisher, 2025)
This study investigates how opportunity to learn (OTL) in project-based mathematics education courses—Manipulative Learning Media (MLM) and Virtual Learning Media (VLM)—supports the development of a growth mindset among pre-service teachers. MLM is a compulsory course focusing on concrete instructional media, while VLM is elective and centers on digital tools. Both apply structured learning cycles involving media design, classroom implementation, revision, and reflection. Using a quantitative comparative approach, data were collected from 85 mathematics education students grouped by course enrollment. Growth mindset and OTL were measured using Likert-scale questionnaires and analyzed with descriptive statistics, t-tests, and Pearson correlation. Results showed that the MLM+VLM group reported slightly higher growth mindset scores (M = 3.54) than the MLM-only group (M = 3.47), though the difference was not significant (p = 0.483). However, OTL scores approached significance (p = 0.054), and a positive correlation was found between OTL and growth mindset (r = 0.642). These findings highlight the value of structured, project-based learning environments in enhancing students’ learning beliefs and instructional readiness.